Accuracy and Interrater Reliability of Point-of-Care Ultrasonography Image Interpretation for Intussusception. Issue 9 (24th September 2022) - Bergmann, Kelly R.; Khant, Marshal; Lammers, Shea; Arroyo, Alexander C.; Avendano, Pablo; Chaudoin, Lindsey; Cohen, Stephanie G.; Deanehan, J. Kate; Kornblith, Aaron E.; Lam, Samuel H. F.; Lin-Martore, Margaret; Malia, Laurie; et al.
Abstract : Objectives: The aim of this study was to determine the accuracy and interrater reliability of (1) point-of-care ultrasound (POCUS) image interpretation for identification of intussusception and (2) reliability of secondary signs associated with intussusception among experts compared with novice POCUS reviewers. Methods: We conducted a planned secondary analysis of a prospective, convenience sample of children aged 3 months to 6 years who were evaluated with POCUS for intussusception across 17 international pediatric emergency departments between October 2018 and December 2020. A random sample of 100 POCUS examinations was reviewed by novice and expert POCUS reviewers. The primary outcome was identification of the presence or absence of intussusception. Secondary outcomes included intussusception size and the presence of trapped free fluid or echogenic foci. Accuracy was summarized using sensitivity and specificity, which were estimated via generalized mixed effects logistic regression. Interrater reliability was summarized via Light's κ statistics with bootstrapped standard errors (SEs). Accuracy and reliability of expert and novice POCUS reviewers were compared. Results: Eighteen expert and 16 novice POCUS reviewers completed the reviews. The average expert sensitivity was 94.5% (95% confidence interval [CI], 88.6–97.5), and the specificity was 94.3% (95% CI, 90.3–96.7), significantly higher than the average novice sensitivity of 84.7% (95% CI, 74.3–91.4) and specificity of 80.4% (95% CI, 72.4, 86.7). κ was significantly greater for expert (0.679, SE 0.039) compared with novice POCUS reviewers (0.424, SE 0.044; difference 0.256, SE 0.033). For our secondary outcome measure of intussusception size, κ was significantly greater for experts (0.661, SE 0.038) compared with novices (0.397, SE 0.041; difference 0.264, SE 0.029). Interrater reliability was weak for expert and minimal for novice reviewers regarding the detection of trapped free fluid and echogenic foci. Conclusions: Expert POCUS reviewers demonstrate high accuracy and moderate interrater reliability when identifying intussusception via image interpretation and perform better than novice reviewers.